(untitled) (The Research of Medical Science Review, 2025)
Background:- Vitamin D exposure has an important connection with cardiovascular disease in spite of its role in maintaining calcium as well as phosphate balance. AF generate a heartbeat that is not regular, which may trigger the heart to beat in excess of 150 times per minute. vitamin D is an antioxidant and an inflammatory mediator. It has been suggested that RAS has an influence in the onset of AF in people with comorbid disorders. Objective:- To gain insight of the correlation among serum vitamin D concentration along with the presence of paroxysmal atrial fibrillation (AF) in young adults. Method: - Patients presenting with arrhythmia symptoms were recruited from the Cardiology departments of Punjab Institute of Cardiology, Evercare Hospital, and Farooq Hospital in Lahore. Each patient initially underwent an Electrocardiogram (ECG) to identify abnormalities, specifically looking for signs of paroxysmal atrial fibrillation (AFib). If the ECG suggested paroxysmal AFib, the diagnosis was confirmed using 24-hour Holter monitoring to capture transient episodes. Results:- The mean age was 28.61±5.184 and graph show normal histogram curve with no skewness. The mean of Body mass index was 21.81±2.521 and graph analysis shows histogram curve with positive skewness. The mean of Resting heart Rate was 105.26±16.119 and graph analysis shows histogram curve with no skewness. Participants gender division showed that there were more men (61.0⁒ )than women (36.6⁒). Participants with Dietary Vitamin D intake are slightly lower level (43.9⁒) than those who did not intake it (56.1⁒). The statistical analysis shows that low serum vitamin D level relate with atrial Fibrillation. Conclusion:- It was conclude think there is a noteworthy correlation low Vitamin D concentration or increase incidence of atrial Fibrillation among young adults, reinforcing the belief that Vitamin D is essential in cardiovascular health , and its impact on electric function of heart. Our study Finding contribute that Vitamin D is essential in cardiovascular health, that regulating the heart electrical activity or having antileukoteric qualities , which may affect the risk of AF.